DETERMINANTS OF STOCK RETURN IN CONSUMER NON-CYLICALS' COMPANIES LISTED ON IDX - Abdurachman, Siti Hafsah; Dewi, Sofia Prima (Graduate Program of Universitas Tarumanagara, 2023)
The aims of this research was to obtain empirical evidence regarding the impact of return on equity, operating cash flow, debt-to-equity ratio, and earnings per share toward stock return in consumer non-cyclicals companies during 2018-2020 listed on Indonesia Stock Exchange. Using purposive sampling method, from 38 companies that were chosen, total sample for three years were 114 data. For data processing, Eviews 12 application is used and the technique analyzed is multiple linear regression. The result is return on equity has a positive impact toward stock return, operating cash flow has no positive impact toward stock return, earnings per share and debt-to-equity ratio have no negative impact toward stock return. The research’s implication is that company need to reduce leverage and increase profitability, because it will affect investor’s decision.